2005
DOI: 10.1111/j.1365-2621.2005.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of mass transport processes during the leaching of amygdalin from bitter apricot kernels: detoxification and flavour improvement

Abstract: Because of their appreciable protein content apricot kernels could be used as a good source of food. However, their wide use for human or animal nutrition is dependent on their adequate detoxification. This is because apricot kernels have a strong bitter flavour that is caused by the presence of amygdalin, a toxic cyanogenic glycoside. The aim of the present work was to investigate an unusual method of detoxifying apricot kernels by soaking them in water. The method was energetically relatively inexpensive as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Apricot kernels and bitter almond kernels have a content of amygdalin of about 3-4% by weight and amydalin amount may even rise up to 8% in apricot seeds (Frohne & Pfander, 2005). Overconsumption of the seeds containing high amount of amygdalin might cause acute or chronic toxicity in human beings and animals (Silem, Günter, Einfeldt, & Boualia, 2006). In a study by Akinci- Yildirim and Askin (2010), amygdalin content in the seeds of ten different bitter or sweet apricot cultivars growing in Turkey was determined by HPLC during the two years.…”
Section: Cyanogenic Glucosidesmentioning
confidence: 99%
“…Apricot kernels and bitter almond kernels have a content of amygdalin of about 3-4% by weight and amydalin amount may even rise up to 8% in apricot seeds (Frohne & Pfander, 2005). Overconsumption of the seeds containing high amount of amygdalin might cause acute or chronic toxicity in human beings and animals (Silem, Günter, Einfeldt, & Boualia, 2006). In a study by Akinci- Yildirim and Askin (2010), amygdalin content in the seeds of ten different bitter or sweet apricot cultivars growing in Turkey was determined by HPLC during the two years.…”
Section: Cyanogenic Glucosidesmentioning
confidence: 99%
“…Apricot kernel oil (AKO), which is rich in oleic acid and c-tocopherol, constitutes 50% of the apricot kernel weight [3]. The main utilizer of AKO is the cosmetic industry who use it as a carrier oil [4]. However, AKO can also be used for edible purposes due to its high nutritional value [5].…”
Section: Introductionmentioning
confidence: 99%
“…As known, the roasting process needs high temperature that can decompose heat sensitive labile compounds in the seed. Amygdalin is also relatively unstable compound that easy to decompose into other compounds [2]. Fig.…”
Section: Comparison Between Extract From Roasted Powder Seed and Groumentioning
confidence: 99%
“…They also reported that loquat seed extract has direct anti-oxidative action. In pharmaceutical industry, amygdalin has been applied as a drug in cancer directly injected into humans blood [2]. Loquat seed also contains sterol, ␤-sitosterol, triglyceride, sterolester, diglyceride and fatty acids, mainly linoleic, palmitic, linolenic and oleic [3,4].…”
Section: Introductionmentioning
confidence: 99%